Strategies Used by Islamic Religious Education Teachers to Instil Moral Values in Students at SMAN 5 Pariaman - Clau; Ikhfa; Salam; Fatmi Fauzani; Rahmanita; Saparia Fitriani (Journal of Creative Power and Ambition (JCPA), 2026)
The instilling of moral values in secondary education plays a strategic role in shaping students’ character so that they can develop in a balanced manner across intellectual, moral, and spiritual aspects. During adolescence, students are in a phase of self-discovery that makes them vulnerable to various negative influences, making the potential for moral degradation a serious challenge for the world of education. This situation underscores the urgency of the role of Islamic Religious Education teachers as educators who not only impart religious knowledge but also continuously nurture students’ moral character and behaviour. This study aims to describe and analyse the strategies employed by Islamic Religious Education teachers in instilling moral values in students at SMAN 5 Pariaman. This study adopts a qualitative approach with a descriptive research design. The research subjects include Islamic Religious Education teachers, students, and relevant school officials. Data collection techniques were carried out through classroom observation, in-depth interviews, and document analysis, whilst data analysis was conducted through the stages of data reduction, data presentation, and drawing conclusions and verification. The results of the study indicate that the strategies employed by Islamic Religious Education teachers in instilling moral values are implemented through setting a good example, habit formation, the integration of values into learning materials, as well as contextual and reflective learning. These strategies are effective in instilling the values of honesty, responsibility, discipline, tolerance, politeness, and religiosity in students. The findings of this study imply the importance of strengthening the role of Islamic Education teachers and school culture support in developing Islamic Education learning oriented towards character building at the Senior Secondary School level.